Menakar Kompetensi Karyawan dalam Penerapan SOP (Standard Operating Procedure): Pada Perusahaan PT. Dua Delapan Ayoda - Kalvano Labathi Ginoga; Gendon Barus (Jurnal Transformasi Bisnis Digital, 2025)
The research was designed to determine: (1) how well employees master competencies in implementing SOP (Standard Operating Procedure) and (2) which employee competencies whose achievements have been identified are not optimal. The methods used are quantitative and qualitative or mixed methods with data collection techniques in the form of questionnaires, observations and interviews with subjects in accordance with the research criteria. The quantitative data analysis technique is based on a questionnaire, while the qualitative analysis technique is based on interview transcripts with subjects, data reduction validated by the subject, data exposure, data presentation, and conclusions. (1) The research results show that employees overall have very good results, with results reaching 68%. This means that employee competency mastery is very good. Of the three employee competency indicators, the knowledge aspect obtained very good results, namely 66%. Then, the skill aspect also gets very good results at 75%. The next indicator is attitude or implication, which results in very good results at a percentage of 54%. (2) The highest level of employee competency is in the skills aspect, while the lowest level of employee competency or needs to be optimized is in the attitude indicator.